In vivo construction of lymphoid node by implantation of adipose-derived stromal cells with hydroxypropyl methyl cellulose hydrogel in BALB/c nude mice. (3rd July 2019) - Zhang, Jing; Xu, Yuqiao; Liu, Tao; Min, Jie; Ma, Yu; Song, Yongli; Lu, Jianrong; Mi, Wenjuan; Wang, Yingmei; Li, Hang; Li, Wangzhou; Zhao, Daqing
ABSTRACT: Adipose-derived stromal cells have multilineage potential to differentiate into several specialized tissue types. Herein, we investigated whether ADSCs could differentiate into lymphoid node in vivo . Human ADSCs from routine liposuction were cultured in differentiation medium and were supplemented with transforming growth factor β1 (TGF)-β1 and basic fibroblast growth factor (bFGF). The induced hADSCs mixed with 13% (w/v) hydroxypropyl methylcellulose (HPMC) were injected into BALB/c nude mice subcutaneously. Eight weeks later, nodules were found under the injected sites. Histology, immunohistochemistry, and species identification analysis confirmed that the nodules were lymphoid nodes that were derived from the injected hADSCs. Our experiment demonstrated that the hADSCs could differentiate into lymphocyte-like cells and form lymphoid nodes in vivo . TGF-β1 and bFGF might play important roles in the differentiation of hADSCs into lymphocyte-like cells. Our study might present an alternative approach for engineering immune organs and thus offer potential treatment for immunodeficiency diseases.